Emerging Insights into Memory Natural Killer Cells and Clinical Applications - Jonida Kokiçi; Anucha Preechanukul; Helena Arellano-Ballestero; Frances Gorou; Dimitra Peppa (Viruses)
Natural killer (NK) cells are innate lymphocytes that can rapidly mount a response to their targets by employing diverse mechanisms. Due to their functional attributes, NK cells have been implicated in anti-viral and anti-tumour immune responses. Although traditionally known to mount non-specific, rapid immune responses, in recent years, the notion of memory NK cells with adaptive features has gained more recognition. Memory NK cells emerge in response to different stimuli, such as viral antigens and specific cytokine combinations. They form distinct populations, accompanied by transcriptional, epigenetic and metabolic reprogramming, resulting in unique phenotypic and functional attributes. Several clinical trials are testing the efficacy of memory NK cells due to their enhanced functionality, bioenergetic profile and persistence in vivo. The therapeutic potential of NK cells is being harnessed in viral infections, with wider applications in the cancer field. In this review, we summarise the current state of research on the generation of memory NK cells, along with their clinical applications in viral infection and cancer.